Rediscovery of the Sumatran Endemics Onychogomphus rappardi (Odonata: Gomphidae) and Herona sumatrana sumatrana (Lepidoptera: Nymphalidae), with Notes on Observations of Other Rare Butterflies and Moths from the North of Sumatra - Bal, Dick (BIO PALEMBANICA, 2024)
Several rare insects were observed around Ketambe in the centre of the Leuser Ecosystem in July 2024. The main subjects discussed are the micromoth Collinsa sp. aff. sphoraria Swinhoe (supposedly new to science) and the rediscoveries of the dragonfly Onychogomphus rappardi Lieftinck, 1937 and the butterfly Herona sumatrana sumatrana Moore, 1881. Both O. rappardi and H. sumatrana sumatrana are Sumatran endemics. Other observations of several rare species are the butterflies Arhopala athada athada (Staudinger, 1889), Deramas livens livens Distant, 1886, Jamides malaccanus celinus (Fruhstorfer, 1916); and the moths Corymica deducta (Walker, 1866), Speiredonia sandokana Zilli & Holloway, 2005 and Teulisna plagiata Walker, 1862.